Gabriela Zapolska: perspektywa interpretacyjnej "trzeciej drogi" = Gabriela Zapolska : a perspective of the interpretative "third means" - Janicka, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The author of the paper joins in the discussion about a style of the interpretation of the G. Zapolska`sworks. Zapolska is the modernist writer, very prolific, but also very controversial. There are two waysof reading her novels: 1) writer is a scandalist; goes in for immoral art; in this immorality she imitatesFrench naturalists; 2) Zapolska is a feminist or she is not too progressive to be named a feminist. Inthe first case scholars use the moral or aesthetic categories; in the second case - ideological reasons.The author offers a "third means" of interpretation. She tries to create a new portrait of Zapolskausing a categories of "a person". It stress a multidimensional character and ambiguity of the Zapolska`s works. We can`t assign them to any literary trend in the 20 century.
Keywords: Zapolska, Gabriela (1857-1921); literaturoznawstwo; literatura polska - tematyka - 19-20 w.